Comparative mapping and targeted-capture sequencing of the gametocidal loci in Aegilops sharonensis - Grewal, Surbhi; Gardiner, Laura-Jayne; Ndreca, Barobora; Knight, Emilie; Moore, Graham; King, Ian P.; King, Julie (Crop Science Society of America, 2017)
Gametocidal (Gc) chromosomes or elements in species such as Aegilops sharonensis are preferentially transmitted to the next generation through both the male and female gametes when introduced into wheat. Furthermore, any genes, e.g. genes that control agronomically important traits, showing complete linkage with gametocidal elements, are also transmitted preferentially to the next generation without the need for selection. The mechanism for the preferential transmission of the gametocidal elements appears to occur by the induction of extensive chromosome damage in any gametes that lack the gametocidal chromosome in question. Previous studies on the mechanism of the gametocidal action in Ae. sharonensis indicates that at least two-linked elements are involved. The first, the ‘breaker’ element, induces chromosome breakage in gametes, which have lost the gametocidal elements while the second, the ‘inhibitor’ element, prevents the chromosome breakage action of the ‘breaker’ element in gametes, which carry the Gc elements. In this study, we have used comparative genomic studies to map 54 single nucleotide polymorphism (SNP) markers in an Ae. sharonensis 4SshL introgression segment in wheat and have also identified 18 candidate genes in Ae. sharonensis for the ‘breaker’ element through targeted sequencing of this 4SshL introgression segment. This valuable genomic resource will aide in further mapping the Gc locus that could be exploited in wheat breeding to produce new, superior varieties of wheat.